A Rapid Entry to Diverse γ‐Ylidenetetronate Derivatives through Regioselective Bromination of Tetronic Acid Derived γ‐Lactones and Metal‐Catalyzed Postfunctionalization. Issue 28 (14th August 2015) - Chopin, Nicolas; Yanai, Hikaru; Iikawa, Shinya; Pilet, Guillaume; Bouillon, Jean‐Philippe; Médebielle, Maurice
Abstract: The synthesis of a series of diverse methyl and benzyl γ‐ylidenetetronate derivatives was accomplished through the condensation of methyl and benzyl tetronates with (hetero)aryl aldehydes in a new two‐ or three‐step aldolisation/dehydration sequence. The bromination of methyl and benzyl γ‐ylidenetetronates occurred under mild conditions to provide the corresponding C‐3‐brominated γ‐unsaturated lactones. Di‐ and tribrominated γ‐lactones were prepared under slightly different conditions. Some brominated materials were employed in representative Stille, Suzuki–Miyaura, and Sonogashira cross‐coupling reactions to yield functionalized methyl and benzyl γ‐ylidenetetronate derivatives. Compounds that resulted from the Sonogashira cross‐coupling reactions were desilylated and converted into 1, 2, 3‐triazole derivatives through a copper(I)‐catalyzed 1, 3‐dipolar cycloaddition reaction with benzyl azide. Abstract : The synthesis of a series of γ‐ylidenetetronate derivatives is presented. The selective and mild brominations of these derivatives gave useful molecular entities that were employed in several cross‐coupling reactions (i.e., Suzuki–Miyaura, Stille, and Sonogashira reactions). Sonogashira‐derived materials were utilized in the preparation of 1, 2, 3‐triazole‐derived tetronic acids.